Programmed Cell Death-Ligand 1 Expression and Clinical Outcomes Among Patients with Resected, Early-Stage Non-Small Cell Lung Cancer: A Real-World Study - Parneet K. Cheema; Iqra Syed; Femida Gwadry-Sridhar; Muhammad Rakibuz-Zaman; Robin Sachdeva; Alec Pencz; Luna Zhan; Katrina Hueniken; Devalben Patel; Karmugi Balaratnam; Khaleeq Khan; Benjamin Grant; et al. (Current Oncology)
Treatment options for non-small cell lung cancer (NSCLC) are evolving, given recent and expected approvals of immune checkpoint inhibitors (ICIs) targeting programmed cell death-(ligand) 1 (PD-1/PD-L1). We retrospectively evaluated outcomes among patients with resected stage IB-IIIA NSCLC tumors expressing PD-L1 using PALEOS (Pan-cAnadian Lung cancEr Observational Study) data (2016–2019). Key outcomes included PD-L1 expression rate and treatment patterns, recurrence, and median overall (mOS) and disease-free survival (mDFS) among PD-L1+ patients. Among 539 PD-L1–tested patients, 317 (58.8%) were PD-L1+ (≥1%). At diagnosis, 35.3%, 39.8%, and 24.9% of PD-L1+ patients had stage IB, II, or IIIA disease. Forty-one percent had received adjuvant therapy. At 22.6 months (median follow-up), first disease recurrence had occurred in 31.9% of patients, primarily at metastatic sites. After first metastatic recurrence, ICI regimens were the most common first systemic therapy (29.8%). mOS was not reached; mDFS was 40.0 months. At four years, DFS probability was 44%. Four-year OS and DFS rates were generally similar when stratified by PD-L1 expression (1–49% vs. ≥50%). These findings underscore the generally poor outcomes experienced by patients with early-stage, resected, PD-L1+ NSCLC after treatment with available adjuvant therapies, and provide context to recent and emerging trials of new treatment options.